Exploring the Underlying Factors Contributing to Millennials and Generation Z’s Difficulties in Entering Marriage in South Africa - Phumuzani Mpofu; Bakhe Dlamini (Universitas Pattimura, 2026)
This study explores the factors underlying the difficulties faced by Millennials and Generation Z in entering marriage in South Africa, while examining the social, cultural, economic, and psychological dynamics shaping such decisions. Employing a qualitative case study design within the framework of Cultural-Historical Activity Theory (CHAT) and a transformative paradigm, data were collected through semi-structured interviews and focus group discussions with purposively selected unmarried participants aged 18–45. The findings reveal that marriage is no longer perceived as an automatic life stage but as a reflexively negotiated institution balancing sacred values and transactional considerations. Key barriers include fear of divorce rooted in family experiences, economic constraints—particularly wedding costs and lobola practices—prioritization of education and career, shifting gender roles, the influence of social media in constructing unrealistic expectations, and the need for emotional readiness and psychological maturity. The study also identifies a shift in the meaning of marriage from a foundational life stage to a capstone achievement requiring financial stability, individual autonomy, and relational competence. This research contributes theoretically by applying CHAT to conceptualize marriage as a dynamic and contradiction-laden activity system, positioning delayed marriage as a complex negotiation between tradition and modernity rather than rejection. The findings highlight the need for adaptive social policies and interventions addressing relational skills, financial literacy, and culturally sensitive reforms.